KRIM EKSTRAK KULIT DELIMA MERAH (PUNICA GRANATUM) MENGHAMBAT PENINGKATAN JUMLAH MELANIN SAMA EFEKTIFNYA DENGAN KRIM HIDROKUINON PADA KULIT MARMUT (CAVIA PORCELLUS) BETINA YANG DIPAPAR SINAR UVB - Siahaan, Eva R.; Pangkahila, Wimpie; Wiraguna, A A G P (UNIVERSITAS SAM RATULANGI, 2017)
Abstract: As the outer organ of the body, skin becomes the main target of environmental influences, particularly the UVB rays. Based on analysis of phytochemicals, red pomegranate peel extract contains antioxidants such as flavonoids, phenols, tannins, and vitamin C which are able to prevent increased skin melanin by inhibiting the actions of tyrosinase. This study was aimed to prove that application of 8% red pomegranate peel extract (Punica granatum) cream could prevent the increase of skin melanin in female guinea pigs (Cavia porcellus) exposed to UVB as well as to prove that the 8% red pomegranate peel extract cream was as effective as 4% hydroquinone cream in preventing increased skin melanin. This was a true experimental study using post test only control group design. Subjects were divided into three groups, with 10 guinea pigs each group. Group 1, the control group, was treated with UVB exposure and basic cream. Group 2 was treated with UVB exposure and 4% hydroquinone cream. Group 3 was treated with UVB and 8% red pomegranate peel extract cream. A total of 390 mJ/cm UVB dosage was given for 2 weeks. Histopahtologic slides were stained with Masson-Fontana. The amount of melanin area colored in black was evaluated by the percentage of pixel areas of melanin compared with pixel areas of all epidermal tissues. The results showed that the highest amount of melanin was in group 1 (18.13±4.76%), followed by group 3 (1.876±0.73%), and group 2 as the lowest (0.67±0.291%). There was a significant difference between control group and group 2 as s well as group 3 (P <0.05). There was no significant difference between group 2 and group 3 (P >0.05). Conclusion: Application of 8% red pomegranate peel extract (Punica granatum) cream could prevent the increase of skin melanin in guinea pigs (Cavia porcellus) exposed to UVB. The 8% red pomegranate peel extract cream was as effective as 4% hydroquinone cream in preventing increased skin melanin.Keywords: red pomegranate peel extract, melanin, skin, UVBAbstrak: Sebagai organ terluar dari tubuh, kulit menjadi target utama dari pengaruh lingkungan, terutama oleh sinar UVB. Berdasarkan analisis fitokimia, ekstrak kulit delima merah memiliki kandungan antioksidan seperti flavonoid fenol, tanin, dan vitamin C yang mampu mencegah peningkatan jumlah melanin dengan cara menghambat kerja enzim tirosinase. Penelitian ini bertujuan untuk membuktikan efek pemberian krim ekstrak kulit delima merah (Punica granatum) 8% dalam menghambat peningkatan jumlah melanin pada kulit marmut (Cavia porcellus) betina yang dipapar sinar UVB dan krim ekstrak kulit delima merah (Punica granatum) 8% memiliki efektivitas yang sama dengan krim hidrokuinon 4% dalam menghambat peningkatan jumlah melanin tersebut. Jenis penelitian ialah eksperimental murni dengan post test only control group design. Subyek penelitian dibagi menjadi tiga kelompok, masing-masing berjumlah 10 ekor marmut betina. Kelompok 1 (kontrol) diberikan pajanan sinar UVB dan krim dasar; kelompok 2 diberikan paparan sinar UVB dan krim hidrokuinon 4%; dan kelompok 3diberikan pajanan sinar UVB dan krim ekstrak kulit delima merah 8%. Dosis total UVB 390 mJ/cm2 yang diberikan selama 2 minggu. Sediaan histopatologik jaringan kulit menggunakan pewarnaan Masson-Fontana. Jumlah melanin dihitung dengan persentase pixel luas area melanin dibandingkan pixel seluruh jaringan epidermis. Hasil penelitian menunjukkan bahwa jumlah melanin paling tinggi terdapat pada kelompok 1 (18,13±4,76%), diikuti kelompok 3 (1,876±0,73%), dan paling rendah pada kelompok 2 (0,67±0,291%). Terdapat perbedaan bermakna antara kelompok 1 dengan kelompok 2 dan 3 (P <0,05) sedangkan antara kelompok 2 dan 3 tidak berbeda bermakna dalam mencegah peningkatan jumlah melanin (P >0,05). Simpulan: Krim ekstrak kulit delima merah (Punica granatum) 8% dapat menghambat peningkatan jumlah melanin pada kulit marmut (Cavia porcellus) betina. Krim ekstrak kulit delima merah (Punica granatum) 8% sama efektif dengan krim hidrokuinon 4% dalam menghambat peningkatan jumlah melanin pada kulit marmut.Kata kunci: kulit delima merah, melanin, kulit, UVB, marmut betina.